Активні процеси лексичного запозичення в сучасній російській мові - Полякова, Т.М. (Мовознавство, 2019)
У статті розглянуто домінантні риси процесів лексичного запозичення в сучасній російській мові: словотвірний потенціал, комунікативну адаптацію та стабілізацію семантичних варіантів іншомовних лексем. Окремо проаналізовано функціонування іншомовних слів у політичному дискурсі, що визначається тим мовленнєвим сегментом, у якому активно реалізується соціалізація запозичень, термінів і сленгізмів іншомовного походження. Встановлено функції іншомовних номінацій та чинники, які сприяють незмінній інтенсивності залучення інновацій іншомовного походження до мови-реципієнта. Дослідження виконано з огляду на загальні мовні процеси, які відбуваються в лексичній системі російської мови. The article deals with major features of lexical borrowing processes in the modern
Russian language: word forming potential, communicative adaptation and stabilization
of sematic variants of foreign lexemes. A separate attention is focused on the analysis
of functioning of foreign lexemes in the political discourse, determined by the language
segment in which the socialization of borrowings, terms and slangisms of foreign origin is
being actively realized. The functions of foreign language nominations and circumstances,
which cause stable intensity of drawing innovations of foreign origin into the languagerecipient,
have been singled out.
The heuristic value of the investigation consists in its providing a possibility for
theoretical interpretation of general processes taking place in Russian at its lexical and
derivative levels as well as widening knowledge about lexico-semantic and derivative
changes in the microsystem of lexical borrowings. Results obtained by the author are
relevant for a further study of influence of language factors upon society and vice versa.